Influence : science and practice - Cialdini, Robert B., 1945- (Pearson Education : Harlow, 2014)
Influence: Science and Practice is an examination of the psychology of compliance (i.e. uncovering which factors cause a person to say “yes” to another's request). Written in a narrative style combined with scholarly research, Cialdini combines evidence from experimental work with the techniques and strategies he gathered while working as a salesperson, fundraiser, advertiser, and in other positions inside organizations that commonly use compliance tactics to get us to say “yes.” Widely used in classes, as well as sold to people operating successfully in the business world, the eagerly awaited revision of Influence reminds the reader of the power of persuasion. Cialdini organizes compliance techniques into six categories based on psychological principles that direct human behavior: reciprocation, consistency, social proof, liking, authority, and scarcity. New to this edition Updated coverage of social influence effects in popular culture, such as the contagion of obesity among the young and the contagion of violence in such tragedies as the Virginia Tech and Northern Illinois mass killings. Also added is coverage of social influence effects in new technologies, such as persuasion resulting from online banner ads and the subliminal presentation of odors. Increased coverage of how compliance principles work in other cultures. New insights are derived from the research findings, sayings, and customs of Latin America, the Far East, and Central Europe. More neuroscience evidence of how the influence process works, integrated throughout. For instance, brain imaging research is presented showing how the “Expensive = good” heuristic operates to lead people to experience more costly items as better than (identical) less costly ones. Enhanced coverage of "how to say no". New evidence is presented to help readers identify their special vulnerabilities to various techniques of persuasion.
Twice as many Readers Reports - first person accounts in which readers of previous editions describe how they've seen a principle work on or for them. These Reports have become the most popular feature of the book.
Keywords: Sociale psychologie